Chylopericardium due to Subclavian Vein Thrombosis in the Setting of Protein S Deficiency. (28th November 2021) - Jackson, Ian; Alali, Yaman; Anani, Abedel Rahman; Nayfeh, Ali; Sharma, Arindam; Thandra, Abhishek; Kabach, Amjad
Abstract : Background . Chylopericardium is the accumulation of lymphatic fluid in the pericardial cavity. It can be idiopathic or secondary to trauma, cardiothoracic surgery, neoplasm, radiation, tuberculosis, lymphatic duct dysfunction, thrombosis, or other causes. We present a case of chylopericardium due to subclavian vein thrombosis in a patient with protein S deficiency. Clinical Case . A 48-year-old man with a history of protein S deficiency presented to the emergency department with shortness of breath and a productive cough. CT of the chest showed pulmonary emboli, moderate pericardial effusion, and a large thrombus of the superior vena cava, brachiocephalic vein, and subclavian veins. He developed echocardiographic evidence of cardiac tamponade so he underwent pericardiocentesis with drainage of milky-appearing fluid. Analysis of the fluid showed elevated triglycerides consistent with chylopericardium. The pericardial effusion reaccumulated, likely secondary to lymphatic duct obstruction due to his subclavian vein thrombus. Catheter-assisted thrombolysis was performed with resolution of the patient's effusion and symptoms. Conclusion . Chylopericardium is a rare but important complication of subclavian vein thrombosis. Management is typically with surgical intervention, although our case represents successful treatment with catheter-assisted thrombolysis.